Craic, duende and conversational trances - Chris Ellis (South African Family Practice)
The family have begun to suspect that, at times, I may drift off to faraway places. This may also happen in the consulting room in the late summer afternoons. A retreat occurs into the deep recesses and lacunae of the cerebral hemispheres. I can be woken from this fugue-like state when the conversation stops, or the tone of the enquiry alters and there are signals that a response is required. Those of us who are members of the school of advanced daydreaming know the rules.